Análise espacial da cultura da soja e sua interação com o meio físico e a precipitação pluviométrica: um estudo no município de Jari (RS), utilizando técnicas de geoprocessamento - Beilfuss, Eric Moises (2025)
The expansion of soybean cultivation is notable in Rio Grande do Sul (RS), which is causing a transformation in land use and land cover (LULC), leading to the need to carry out studies at more detailed scales in order to understand the dynamics of its advance and its interaction with the physical environment and precipitation. Jari (RS) is one of the municipalities that has seen significant expansion, and therefore became the study area for this dissertation. The general objective is to analyze soybean expansion in Jari (RS), and its interaction with the physical environment (altitude, slope, landforms and soils) and precipitation, with the support of Geoprocessing and Remote Sensing (RS) techniques. As for materials and methods, a database was developed in QGIS software, containing information on soils, altitude, slope and landforms. LULC data was obtained from MapBiomas. The Dinamica EGO platform was used for scenario modeling. Google Earth Engine was used to obtain the Normalized Difference Vegetation Index (NDVI). The results indicate that the area under soybean cultivation will expand by 897.3% between 1985 and 2021, mainly due to the conversion of grassland areas to temporary crops. Soybean expansion can be divided into three phases: the first (1985-1998) was characterized by gradual growth, mainly in areas of gently undulating hills; the second (1999-2015) saw accelerated crop growth, with the occupation of steeper terrain and less favourable soils; the third phase (2016-2021) showed a slower pace of expansion, still with advances in less favourable terrain. With regard to rainfall, the drought that occurred during the La Niña phenomenon in the 2022/2023 harvest had an impact on soybean growth, with several crops having to be replanted, resulting in low NDVI values. In view of the above, variables such as landforms, slope and rainfall in the municipality were identified as being restrictive to cultivation. In addition, simulations of future LULC scenarios were carried out, showing that the area of soybean cultivation could increase by 2030, possibly occupying 52.6% of the municipality's total area, losing 34.4 km² of field in the period analyzed due to the conversion of natural field areas. In this way, the use of Geoprocessing and RS was indispensable for analyzing the monoculturization of Jari (RS), generating a database that allowed us to follow the interaction between the advance of soybean cultivation and the attributes of the physical environment and precipitation, on a time scale of almost 40 years.